2008
DOI: 10.25011/cim.v31i5.4868
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro-B-type natriuretic peptide levels increases after hyperbaric oxygen therapy in diabetic patients

Abstract: Purpose: Diabetic patients receive hyperbaric oxygen therapy for non-healing lower extremity ulcers. Exposure to hyperbaric hyperoxia during hyperbaric oxygen therapy may affect cardiovascular functions by different mechanisms. Patients may experience serious problems such as pulmonary edema and death during hyperbaric oxygen therapy. The effect of hyperbaric oxygen therapy on cardiovascular functions in diabetic patients is not well documented. N-terminal pro-B-type natriuretic peptide (NT-proBNP) has been su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This is the opposite of one of the suggested biological functions of BNP, which is to facilitate hemoconcentration in order to increase the per volume oxygen carrying capacity of blood in response to hypoxia [ 18 ]. In contrast, the opposite of hypoxia, a higher than normal partial oxygen pressure, hyperoxia, may also cause elevation of NT-proBNP levels in-vivo [ 19 ]. Supplemental oxygen is often administered during cardiopulmonary resuscitation and a high PaO 2 is no rare phenomenon, especially in mechanically ventilated patients [ 20 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the opposite of one of the suggested biological functions of BNP, which is to facilitate hemoconcentration in order to increase the per volume oxygen carrying capacity of blood in response to hypoxia [ 18 ]. In contrast, the opposite of hypoxia, a higher than normal partial oxygen pressure, hyperoxia, may also cause elevation of NT-proBNP levels in-vivo [ 19 ]. Supplemental oxygen is often administered during cardiopulmonary resuscitation and a high PaO 2 is no rare phenomenon, especially in mechanically ventilated patients [ 20 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently a number of studies have investigated the value of BNP in diabetes disease (20)(21)(22)(23)(24) but role of BNP in the prognosis of diabetic patients with foot ulcer has not been examined except after the use of hyperbaric oxygen therapy (25). This study has shown that patients with BNP > 100 pg/mL mg/dl have a higher risk of all-cause mortality in patients with foot ulcer.…”
Section: Discussionmentioning
confidence: 75%
“…These ndings are consistent with two previous studies [24,25], reporting a similar association between admission levels of NT-proBNP and outcome in resuscitated OHCA patients. There are several possible mechanisms for increased NT-proBNP/BNP secretion during cardiac arrest and CPR, including hypoxemia [30], ischemia [31], ischemia-reperfusion induced in ammation [32], therapeutic interventions with administration of uids [33] and vasopressors [34], and mechanical ventilation with supplementary oxygen administration [35]. Myhre et al 2016 [24] demonstrated an increase in NT-proBNP levels from admission up to 96 hours after hospitalization in OHCA-VT/VF patients.…”
Section: Discussionmentioning
confidence: 99%